Enhancing Autophagy Diminishes Aberrant Ca2+ Homeostasis and Arrhythmogenesis in Aging Rabbit Hearts - Murphy, Kevin R.; Baggett, Brett; Cooper, Leroy L.; Lu, Yichun; O-Uchi, Jin; Sedivy, John M.; Terentyev, Dmitry; Koren, Gideon (Frontiers in Physiology, 2019)
Aim Aging in humans is associated with a 10–40-fold greater incidence of sudden cardiac death from malignant tachyarrhythmia. We have reported that thiol oxidation of ryanodine receptors (RyR2s) by mitochondria-derived reactive oxygen species (mito-ROS) contributes to defective Ca2+ homeostasis in cardiomyocytes (CMs) from aging rabbit hearts. However, mechanisms responsible for the increase in mito-ROS in the aging heart remain poorly understood. Here we test the hypothesis that age-associated decrease in autophagy is a major contributor to enhanced mito-ROS production and thereby pro-arrhythmic disturbances in Ca2+ homeostasis. Methods and Results Ventricular tissues from aged rabbits displayed significant downregulation of proteins involved in mitochondrial autophagy compared with tissues from young controls. Blocking autophagy with chloroquine increased total ROS production in primary rabbit CMs and mito-ROS production in HL-1 CMs. Furthermore, chloroquine treatment of HL-1 cells depolarized mitochondrial membrane potential (Δψm) to 50% that of controls. Blocking autophagy significantly increased oxidation of RyR2, resulting in enhanced propensity to pro-arrhythmic spontaneous Ca2+ release under β-adrenergic stimulation. Aberrant Ca2+ release was abolished by treatment with the mito-ROS scavenger mito-TEMPO. Importantly, the autophagy enhancer Torin1 and ATG7 overexpression reduced the rate of mito-ROS production and restored both Δψm and defective Ca2+ handling in CMs derived from aged rabbit hearts. Conclusion Decreased autophagy is a major cause of increased mito-ROS production in the aging heart. Our data suggest that promoting autophagy may reduce pathologic mito-ROS during normal aging and reduce pro-arrhythmic spontaneous Ca2+ release via oxidized RyR2s.